2017
DOI: 10.5489/cuaj.4499
|View full text |Cite
|
Sign up to set email alerts
|

Biopsychosocial impact of prostate cancer and androgen-deprivation therapy

Abstract: Introduction: Prostate cancer is the most non-cutaneous malignancy in men, and androgen-deprivation therapy (ADT) is a cornerstone of management in advanced disease. The aim of this study was to evaluate the association of ADT with changes in depression and mental and physical quality of life (QoL) within a prospective patient cohort design. Methods: Patients were prospectively recruited and consented at a single academic health sciences centre in Ontario, Canada. Inclusion criteria included those men with ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The GDS scores were higher in the second assessment, implying an increase of the men who had a positive screening for depressive symptoms, but the differences were not statistically significant. This finding contrasts with previous longitudinal studies that found a higher prevalence of depression in men treated with ADT [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], and in line with others, that did not confirm such a relationship [ 73 , 74 ]. Earlier studies suggested a relationship between borderline or lower testosterone levels and depressive symptoms in men [ 75 , 76 , 77 ], especially when the reduction of testosterone concentrations was longitudinal [ 78 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The GDS scores were higher in the second assessment, implying an increase of the men who had a positive screening for depressive symptoms, but the differences were not statistically significant. This finding contrasts with previous longitudinal studies that found a higher prevalence of depression in men treated with ADT [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], and in line with others, that did not confirm such a relationship [ 73 , 74 ]. Earlier studies suggested a relationship between borderline or lower testosterone levels and depressive symptoms in men [ 75 , 76 , 77 ], especially when the reduction of testosterone concentrations was longitudinal [ 78 ].…”
Section: Discussioncontrasting
confidence: 99%
“…As a grievous condition and a major threat to human, cancer directly or indirectly causes mood disorders to patients as a consequence of a large reduction of life expectancy, side effect of anti-tumor drugs and a change of quality of life (11,17,18). For instance, in a recent cohort study in Indonesia, the researchers discover an obvious decline in anxiety level and an increase of QoL in oral squamous cell carcinoma patients treated by chemotherapy or invasive therapies (19).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence demonstrating that health and illness are much more complex, which is illustrated by the biopsychosocial model. 4 This has led to wider acknowledgement that patients whose psychological needs are met cope better with their illness.…”
Section: Introductionmentioning
confidence: 99%